Tourism consumption and representation: narratives of place and self - Meethan, K.; Anderson, A.; Anderson, A.; Meethan, K.; Miles, S.; Miles, S. (Wallingford :CABI, 2006)
This book addresses some new developments in approaches towards tourism analysis that focus on the interface between the production and consumption of tourist space, the narratives that are created around specific sites and specific forms of tourist activity, and the ways in which these are created, picked up, modified and incorporated into the narratives of self-hood that people weave around their lives and the identities of the places in which they live. The 15 chapters in this volume reflect important shifts that have occurred in contemporary society and the tourism studies field. These involve the processes of globalization, leading to increased flows of people and cultures around the world, increased individualism and consumerism and new information technologies. The book draws on a range of examples from Australia, Asia, Europe, the Caribbean and Central America. It will be of interest to researchers and students in the fields of tourism, sociology and social anthropology.
Keywords: EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); EE720 - Consumer Economics; UU485 - Social Psychology and Social Anthropology, (New March 2000); UU700 - Tourism and Travel; Asia; Australia; Caribbean; Central America; Europe